1992
DOI: 10.1145/142040.142064
|View full text |Cite
|
Sign up to set email alerts
|

Game playing as a technique for teaching parallel computing concepts

Abstract: Blackboard tracing of algorithms, while an effective tool for the teaching of sequential programming, i s singularly ineffective and confusing when applied to paralle l computing . The use of classroom games to illustrate concepts and pathologies proves to be a useful alternative technique . Games in which students play the role of processors can be used to illustrate simple parallel algorithms as wel l as more complex concepts . Live demonstrations are stimulating for both the participants and the class as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Several studies have also shown the value of games in teaching computer science and biology concepts . The citizen science game Foldit offers a way for players to engage in real science and has allowed over 100 000 people to participate in protein folding puzzles.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown the value of games in teaching computer science and biology concepts . The citizen science game Foldit offers a way for players to engage in real science and has allowed over 100 000 people to participate in protein folding puzzles.…”
Section: Related Workmentioning
confidence: 99%
“…Kitchen et al . noted the value of classroom games where students take on the role of processors to illustrate parallel computing concepts . Papastergiou compared a computer game with web‐based curriculum for learning computer memory concepts, finding that the game group had increased motivation and more effective learning outcomes .…”
Section: Related Workmentioning
confidence: 99%
“…Kitchen et al noted the value of classroom games where students take on the role of processors to illustrate parallel computing concepts [20]. Tang et al [38] explored the use of a city infrastructure virtual reality game to stimulate metacognition in engineering students.…”
Section: Related Workmentioning
confidence: 99%
“…The impetus for using games and role playing to illustrate parallelism concepts can ultimately be traced back to a paper by Kitchen, Schaller, Tyman entitled Game playing as a technique for teaching parallel computing concepts [5]. The authors argue convincingly that static drawings on a blackboard do not effectively convey the more dynamic and complex inter-workings of parallel computations, whereas role playing, where students play the role of a processing core, illustrates parallelism concepts more easily and naturally.…”
Section: Day Onementioning
confidence: 99%